KAJIAN DAN ADVIS PENYERTAAN MODAL DAERAH PADA PT. LEMBAGA KEUANGAN MIKRO (LKM) GARUT - Budiman Budiman; Lilis Sulastri; Agus Joharudin; Rifki Fauza (Komitmen: Jurnal Ilmiah Manajemen, 2020)
This study was aimed to examine and advise PT. Lembaga Keuangan Mikro (LKM) on capital inclusion adequacy. This study used a quantitative approach by using parametric statistics, and financial report analysis from 2014 to 2018. In this period, the performance of LKM was great. Its asset increased from Rp. 16.40 billion to Rp. 38.37 billion; its credit increased from Rp. 12.16 billion to Rp. 32.60 billion; its savings increased from Rp. 8.53 billion to Rp. 11.28 billion; and its deposits increased from Rp. 11.86 billion to Rp. 17.60 billion. Furthermore, LKM also has good key performing indices. The Capital Adequacy Ratio (CAR), Productive Asset Quality (PAQ), Non-Performing Loan, Cash Ratio, Operating Expense Ratio, (OER), Return on Asset, and Loan to Deposit Ratio (LDR) are all within healthy limits.Â This brings a good consequence in improving realization need in capital injection from the owner. As to increase PT. LKM performance, the government is suggested to give aÂ  capital at least 1 billion Rupiah.